2007
DOI: 10.1080/17518420701263146
|View full text |Cite
|
Sign up to set email alerts
|

Can’t they like me as I am? Psychological interventions for children and young people with congenital visible disfigurement

Abstract: This paper describes the psychological challenges for children and young people with a congenital visible disfigurement. These challenges are outlined in a developmental framework and case histories are used to illustrate a range of interventions. The model underlying assessment and intervention moves away from dysfunction and disability and outcomes are defined by psychological strengths, resilience and coping strategies. For those living with a visible disfigurement, who needs rehabilitation?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…The higher‐than‐expected levels of distress identified in the current sample were consistent with previous studies that have found elevated depression and anxiety symptoms among parents of children with other types of chronic conditions . This finding also reflects the results of qualitative studies that have highlighted parental distress in CFA populations, indicating that mothers of children with CFAs may be at a significantly higher risk of experiencing symptoms of depression and anxiety than mothers of healthy children.…”
Section: Discussionsupporting
confidence: 90%
“…The higher‐than‐expected levels of distress identified in the current sample were consistent with previous studies that have found elevated depression and anxiety symptoms among parents of children with other types of chronic conditions . This finding also reflects the results of qualitative studies that have highlighted parental distress in CFA populations, indicating that mothers of children with CFAs may be at a significantly higher risk of experiencing symptoms of depression and anxiety than mothers of healthy children.…”
Section: Discussionsupporting
confidence: 90%
“…Following a diagnosis of CL/P in their child, parents often express feelings of guilt, grief, and concern over their child's future (Nelson et al, 2012). For the child, looking and/or sounding different to their peers may interfere with social interaction and invite some degree of teasing or bullying (Hearst, 2007). Difficulties surrounding emancipation from the family unit and the initiation of intimate relationships may also be problematic (Noar et al, 1991;Danino et al, 2005).…”
Section: Impacts Of Cleftmentioning
confidence: 99%
“…Cumulative research evidence suggests that a child with a disfigurement is at increased risk of disturbed attachments to primary caregivers, being the subject of staring, intrusive questioning, ridicule, hostility in public, avoidance, decreased popularity and teasing from peers, impaired social adjustment, social anxiety and behavior problems (Hearst 2007). Patients and parents found the discussion of conflicts regarding brace-wearing were significant since peer pressure to conform exists and patients face parental pressure to wear a brace which in fact makes them stand out (Donnelly et al 2004).…”
Section: Discussionmentioning
confidence: 99%